2013
DOI: 10.1002/asi.22863
|View full text |Cite
|
Sign up to set email alerts
|

The use of different information and communication technologies to support knowledge sharing in organizations: From e‐mail to micro‐blogging

Abstract: Previous research has revealed the following three challenges for knowledge sharing: awareness of expertise distribution, motivation for sharing, and network ties. In this case study, we examine how different generations of information and communication technologies (ICTs), ranging from e‐mail to micro‐blogging, can help address these challenges. Twenty‐one interviews with employees from a multinational company revealed that although people think social media can better address these challenges than older tool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 58 publications
2
40
0
Order By: Relevance
“…While social media has been criticized as a platform where people can keep their network informed of mundane activities, such as what they ate for breakfast [27], at the other end of the spectrum, people find and share consumer, business, and special event information and learn new things [64]. Social media also enable people to encounter and maintain awareness of professional or work-related information [67]. Through social media, university students share information about social functions, friends, and academic information [3,18,49], making these sites valuable resources.…”
Section: Everyday Life and Work Informationmentioning
confidence: 99%
“…While social media has been criticized as a platform where people can keep their network informed of mundane activities, such as what they ate for breakfast [27], at the other end of the spectrum, people find and share consumer, business, and special event information and learn new things [64]. Social media also enable people to encounter and maintain awareness of professional or work-related information [67]. Through social media, university students share information about social functions, friends, and academic information [3,18,49], making these sites valuable resources.…”
Section: Everyday Life and Work Informationmentioning
confidence: 99%
“…In addition to being used by individuals working alone, IM is also a tool that allows for multitasking during group events, such as meetings, particularly when the norms of the organization support the use of IM and other tools for extra-meeting communication (Dennis et al, 2010;Stephens & Davis, 2009;Yuan et al, 2013). Observations by Dennis et al of two U.S.-based companies found that many IMs sent and received during meetings were not related to the meeting at hand.…”
Section: Affordances and Constraints Of Workplace Immentioning
confidence: 96%
“…While email remains the dominant computer-mediated communication (CMC) tool in most organizations (D'Urso & Pierce, 2009;, IM is becoming more important in a number of business settings, particularly in multinational organizations (Hunt, 2009;Yuan et al, 2013). One survey of MBA students in the United States found that 53% worked in organizations that supported IM use (Glass & Li, 2010), while an industry survey found that 84% of responding organizations used corporate-sanctioned, or enterprise, IM (EIM) (Radicati & Hoang, 2011).…”
Section: Instant Messaging In Organizationsmentioning
confidence: 99%
“…Today there are many different types of social media that are used to support collaborative knowledge work, both within the firm and between the firm and its various stakeholders (e.g., Yuan et al, 2013). A specific example is the social reality application (virtual world technology) like Second Life and World of Warcraft, where the self is presented in the virtual body of an avatar -as a cyborg (Schultze and Mason, 2012).…”
Section: Recent Developments: It As An Active Participant In Knowledgmentioning
confidence: 99%